The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/01937235221109438
|View full text |Cite
|
Sign up to set email alerts
|

Reconceptualizing Women's Wellbeing During the Pandemic: Sport, Fitness and More-Than-Human Connection

Abstract: This paper explores the gendered, disruptive effects and affective intensities of COVID-19 and the ways that women working in the sport and fitness sector were prompted to establish more-than-human connection through technologies, the environment, and objects. Bringing together theoretical and embodied insights from object interviews with 17 women sport and fitness professionals (i.e., athletes, coaches, instructors) in Aotearoa New Zealand, this paper advances a relational understanding of the multiple human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…In their efforts to (re)create new everyday patterns, many engaged in exercise practices (i.e., walking, running, working out at home, online fitness, yoga) (Thorpe et al, 2022). Whereas some took up new activities, others modified their pre‐pandemic exercise regimes around new daily spatio‐temporal routines, modifying bedrooms, garages and backyards as spaces to workout alone and/or with family (Clark & Lupton, 2021).…”
Section: Analysis and Discussion: The Pandemic As Gender Arrhythmia I...mentioning
confidence: 99%
“…In their efforts to (re)create new everyday patterns, many engaged in exercise practices (i.e., walking, running, working out at home, online fitness, yoga) (Thorpe et al, 2022). Whereas some took up new activities, others modified their pre‐pandemic exercise regimes around new daily spatio‐temporal routines, modifying bedrooms, garages and backyards as spaces to workout alone and/or with family (Clark & Lupton, 2021).…”
Section: Analysis and Discussion: The Pandemic As Gender Arrhythmia I...mentioning
confidence: 99%
“… Downing et al (2021) research with therapists described the ways that fostering a sense of safety and care online demanded intensive focus and “dynamic interactions between humans, objects and technologies” (p. 7). As feminist materialist scholars, we have considered the human and nonhuman (i.e., objects, environments, technologies, animals) aspects of women’s lives during the pandemic, and in the research process ( Jeffrey et al, 2021 ; Thorpe et al, 2022 ). In this article, we extend upon this work, examining not only what is required for multidimensional care but also what is meant by the term relational in new materialist feminist ethical scholarship.…”
Section: Literature Review: Rethinking Research Ethics In Pandemic Timesmentioning
confidence: 99%
“…Under these challenging conditions, women's mental health was heavily impacted, with women experiencing higher rates of depression and anxiety than men (Thibaut & van Wijngaarden-Cremers, 2020). Research on the gendered dimensions of COVID-19 has revealed the importance of physical activity for women's wellbeing during the pandemic (Humberstone, 2022; Pandya, 2021), and how some women shared physical activity experiences with friends, family, and colleagues as a mode of connection and community (re)building (Thorpe, Jeffrey, Fullagar, & Pavlidis, 2023).…”
Section: Literature and Conceptual Framing: The Pandemic As Gendered ...mentioning
confidence: 99%